Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.earscirev.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

A review of latitudinal characteristics of sporadic sodium layers, including new results from the Chinese Meridian Project

Abstract: Characteristics of the sporadic sodium layers (SSLs or NaS) in different latitudes and altitudes are summarized in this paper and the possible mechanisms are discussed. The SSLs in high latitude have a maximum frequency near midnight with significant seasonal differences of height and intensity being reported in previous studies. The average height of summer SSLs was much lower than that of winter SSLs and the average density enhancement factor for summer SSLs was much larger than that for winter SSLs. The sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 126 publications
(240 reference statements)
4
18
0
Order By: Relevance
“…We propose that the supposed sodium reservoir should contain some specific properties: it needs to have efficient adsorption ability to store enough sodium sources, it has a fast release mechanism, and lastly, the release process is related to a warming temperature enhancement; it might have no correlation to E S or auroral activities. Recently, Qiu et al () and Qiu et al () observed the following empirical scenario for typical subtropical SSLs: extremely low temperatures below 150 K have always occurred several hours before the SSLs and most of these SSLs were formed or generated with a temperature maximum over 190 K. These statistical results showed that the occurrence of low temperature and the corresponding subsequent temperature increase is a specific character of these SSLs. According to these results, formation of icy‐dust particles, which could form in the extremely cold weather condition and then adsorbs and accumulates sodium species, and could also sublimate in the hot mesospheric weather to release free sodium atoms, was proposed as a candidate for the sodium reservoir (Qiu et al, , ).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…We propose that the supposed sodium reservoir should contain some specific properties: it needs to have efficient adsorption ability to store enough sodium sources, it has a fast release mechanism, and lastly, the release process is related to a warming temperature enhancement; it might have no correlation to E S or auroral activities. Recently, Qiu et al () and Qiu et al () observed the following empirical scenario for typical subtropical SSLs: extremely low temperatures below 150 K have always occurred several hours before the SSLs and most of these SSLs were formed or generated with a temperature maximum over 190 K. These statistical results showed that the occurrence of low temperature and the corresponding subsequent temperature increase is a specific character of these SSLs. According to these results, formation of icy‐dust particles, which could form in the extremely cold weather condition and then adsorbs and accumulates sodium species, and could also sublimate in the hot mesospheric weather to release free sodium atoms, was proposed as a candidate for the sodium reservoir (Qiu et al, , ).…”
Section: Introductionmentioning
confidence: 94%
“…In general, the occurrence of SSLs observed in subtropical latitudes, from 20°N to 35°N, has a weak correlation to E S activities (Dou et al, ; Gong et al, ; Miyagawa et al, ; Qiu et al, , ). These SSLs, usually lasting for a long period and locating near the centroid height of normal sodium layer at 92 km, are often detected accompanied by large temperature enhancements (Gardner et al, ; Li et al, ; Qian et al, ; Qiu et al, , ). Thus, the temperature‐controlled theory, instead of the E S theory, seems to be more appropriate for explaining the subtropical SSLs (Qiu et al, , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, lidars are widely used in lower atmosphere via Mie scattering, Raman scattering and differential absorption (Godin et al, 1989;Campbell et al, 2002;Renaut et al, 1980;Murray and van der Laan, 1978;Xia et al, 2007;Reitebuch, 2012), in middle atmosphere via Rayleigh scattering (Xia et al, 2012;Xia et al, 2014;Dou et al, 2009;Lux et al, 2018), in mesosphere and lower thermosphere via fluorescence backscatter (She et al, 1992;Gao et al, 2015;Li et al, 2018;Qiu et al, 2016). Aerosol, trace gas concentration, atmospheric density and temperature, wind, and neutral metal atom can be detected by these lidars.…”
mentioning
confidence: 99%
“…However, if there is a significant reduction in the magnitude of a wind shear, the further evolution and deformation are ceased and the remnant of the previously generated KH billows can get nearly frozen‐in the background. Qiu et al () also support the frozen‐in concept. They observed the same C‐type structure in Na lidargram from different lidar locations in China.…”
Section: Discussionmentioning
confidence: 88%